Environmental Protection Bureau leadership at the provincial level in China: Examining diverging career backgrounds and appointment patterns - Genia Kostka (Frankfurt School of Finance & Management, 2011)
This paper analyzes the career backgrounds of local government officials in provincial Environmental Protection Bureaus (EPBs) in China and explains appointment processes of Chinese EPB bureaucrats. Using biographical information of provincial EPB heads and drawing on extensive fieldwork conducted in 2010 in Shanxi Province and Inner Mongolia, this paper finds that only one-fourth of current EPB heads were promoted through the bureau ranks within the EPB, while the remaining three-fourths were appointed from positions outside the environment field. Further, nearly all EPB heads' professional backgrounds and associated networks can be clearly categorized as environmental, business, provincial government, or local government oriented. The paper delineates these four types of Chinese EPB leaders and explains why an awareness of the different professional orientations is critical to understanding environmental protection in China. These findings have implications for inferring the unique characteristics of a province's EPB leadership, the implementation capacities of provincial EPBs, and the appointment preferences of provincial leaders.
Keywords: P28; Q28; O18; R58; Q48; Q58; 330; agency; environmental protection; policy implementation; networks; China